Pembuatan dan Pemasangan Biopori sebagai Usaha Konservasi Air di Kelurahan Sampangan Kec. Gajahmungkur Kota Semarang - Ratri Septina Saraswati; Bayu Arie Wibawa; Anita Viana; Agustina Wardani (Yayasan Literasi Sains Indonesia, 2026)
The datas of Semarang City climate 2024 shows that the highest rainfall in the city occurred in February, at 356 mm/month, exceeding the highest average for Indonesia. Gajahmungkur District has 8 sub-districts urban villages, including Sampangan sub-district, which has a high rainfall of 83.65 mm/year. Sampangan sub-district is a densely populated area, so during heavy rains many areas are flooded. The cause is the condition of yards and road shoulders dominated by cement pavement and paving blocks, so water cannot be absorbed directly into the ground. Rainwater flows and is trapped, forming puddles. During high rainfall intensity, the city's drainage system is also unable to accommodate the flow from waterways in residential areas, resulting in flooding. Most residents have heard of biopores but do not have sufficient knowledge about their benefits and how to make them. Therefore, training was held on making biopore infiltration holes. This method aims to increase rainwater absorption into the soil (water conservation). The materials are simple and most easily used in household environments. Biopore holes must first be filled with organic waste, including fallen leaves, weeds, and kitchen waste that is usually disposed of in the trash. The goal is to attract soil organisms to work and loosen the soil. Adding organic waste to the biopore holes can reduce the amount of waste decomposing and polluting the air, while also producing compost. Residents have responded positively to the installation of biopore holes, and implementation in the field has shown results in several areas where flooding and rainwater runoff occur.